2016
DOI: 10.7863/ultra.14.12068
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Sinus Flow Is Reduced and Recovered With Time in Viral Myocarditis Mimicking Acute Coronary Syndrome

Abstract: A Transthoracic Doppler Echocardiographic Studyhe complete evaluation of acute myocarditis is very complex and includes the history, physical examination, blood work, echocardiography, coronary angiography, and endomyocardial biopsy. 1,2 The current histopathologic criteria for myocarditis (the Dallas criteria) require an inflammatory infiltrate and associated myocyte necrosis or damage that is not characteristic of an ischemic event. 3 However, the clinical presentation of myocarditis often mimics acute coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Most importantly, these patients need closer monitoring and should be managed in a high-care or cardiac-care setting. 1 Diagnosis of acute viral myocarditis is based on the presenting symptoms, elevated cardiac markers suggestive of myocardial necrosis, and electrocardiographic and echocardiographic changes. Although a wide range of diagnostic tests may be warranted when initially evaluating these patients, conventional echocardiography remains a crucial imaging modality to exclude other underlying cardiac diseases, to evaluate cardiac chamber size, wall thickness, ventricular function and presence of pericardial collections, to differentiate fulminant from acute myocarditis, and to help guide the patient's management.…”
mentioning
confidence: 99%
“…Most importantly, these patients need closer monitoring and should be managed in a high-care or cardiac-care setting. 1 Diagnosis of acute viral myocarditis is based on the presenting symptoms, elevated cardiac markers suggestive of myocardial necrosis, and electrocardiographic and echocardiographic changes. Although a wide range of diagnostic tests may be warranted when initially evaluating these patients, conventional echocardiography remains a crucial imaging modality to exclude other underlying cardiac diseases, to evaluate cardiac chamber size, wall thickness, ventricular function and presence of pericardial collections, to differentiate fulminant from acute myocarditis, and to help guide the patient's management.…”
mentioning
confidence: 99%
“…Currently, there are no TTE-based diagnostic criteria for Ischemic Heart Disease of follow-up. Nor pre or nor post, but there are publications that describe TTE as a screening method for Coronary Artery Disease in isolated populations [36][37][38]. Quantifications of CS blood flow changes after CABG can be performed using Echocardiography [39][40][41].…”
Section: Venous Side Of Coronary Circulationmentioning
confidence: 99%
“…The vascular tone of coronary microvessels is physiologically regulated by myogenic, neural, metabolic, and endothelial mechanisms according to local demands . Myocardial inflammation interferes with this precisely regulated system and induces endothelial dysfunction and microcirculatory disturbances which lead to a reduced tissue perfusion and myocardial ischemia . Experimental studies have demonstrated that acute myocarditis is associated with capillary damage, microvascular luminal narrowing, and microvascular spasm …”
Section: Introductionmentioning
confidence: 99%